The acquisition of European Portuguese lateral consonants by Chinese learners - Zhou, Chao (2018)
The present study examined the production of European Portuguese (EP) lateral consonants by 14 Chinese learners, through a picture naming task eliciting the target segments in all possible syllable and word-level positions. Our results illustrate that /l/ is stable in singletons (100% target-like) due to the positive transfer from Mandarin Chinese. However, it is very often vocalized in codas (only 16.7% target-like production, [ɫ]), which might be attributed to a phonetically based tendency (Graham, 2017; Johnson & Britain, 2007). The high accuracy (97% target-like) of /l/ in onset clusters, an absent structure in the L1, can be the result of the heterosyllabic nature of EP obstruent-liquid sequences (Veloso, 2006) or of the association of two segments to a single skeletal position, which was also argued as an intermediate stage in EP L1 acquisition (Freitas, 2003). /ʎ/ is still in acquisition (52.4% target-like), and is often produced as an L1 category [lj], due to acoustic and articulatory similarity.